ANALISIS PENGARUH PEMBERDAYAAN DAN MOTIVASI TERHADAP KINERJA DENGAN MEDIASI KEPUASAN KERJA (Studi Pada Perangkat Desa Se Kecamatan Tlogomulyo Kabupaten Temanggung) - Teguh Supriyanto, 11.52.02.0057 (Students Journal of Economic and Management, 2013)
The purpose of this study was to test and analyzethe influence of empowerment and motivation to Performance used Job Satisfactionas the Mediation variable in Tlogomulyo Sub District of Temanggung District. This study focused on employees known as âperangkat desaâ who are not civil servants in Tlogomulyo Sub District of TemanggungDistrict, which amounts to122people.The processed data obtained by using statistical methods which is Linear Regression and Statistical Program Product and Service Solutions (SPSS). The results showed,The first there is a positive influence of empowerment to job satisfaction. The second, there is a positive influence of motivation to job satisfaction. The third,there is a positive influence of empowerment to performance. The fourth, there is a positive influence of motivation to performance. The fifth there is a positive influence of job satisfaction to performance.Performancecan be achieved morequicklythrough increasedempowermentof perangkat desa. Keywords: Empowerment, Motivation, Job Satisfaction and Performance